2011
DOI: 10.2147/opth.s22909
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intralesional propranolol for periocular capillary hemangioma

Abstract: Background:The purpose of this study was to evaluate the use of intralesional propranolol injection in the management of periocular capillary hemangioma.Methods:A prospective study was performed in 22 consecutive patients with periocular hemangioma. Twelve patients underwent intralesional propranolol injection and ten patients underwent intralesional triamcinolone injection. The size of the lesion was measured serially every week during the first month, every 2 weeks for the second month, and then monthly for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“…7 Since the first report in 2008, 8 oral propranolol treatment for severe hemangioma has shown great advantages 9-11 with a trend of replacing oral corticosteroids. 16 In contrast, local injection of corticosteroids in small-size hemangioma achieved good results with fewer side effects. 13 Also, propranolol treatment requires long treatment time, with recurrence after withdrawal.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 Since the first report in 2008, 8 oral propranolol treatment for severe hemangioma has shown great advantages 9-11 with a trend of replacing oral corticosteroids. 16 In contrast, local injection of corticosteroids in small-size hemangioma achieved good results with fewer side effects. 13 Also, propranolol treatment requires long treatment time, with recurrence after withdrawal.…”
Section: Discussionmentioning
confidence: 98%
“…However, it has the risk of temporary growth delay, Cushing-like manifestations, and adrenal suppression. 16 It seemed that intralesional propranolol could stop the growth of tumor but did not lead to the rapid shrinkage of tumor. 12 Nevertheless, the side effects such as bradycardia, diarrhea, hypoglycemia, and hyperkalemia are worrying problems, although the incidence is low.…”
Section: Discussionmentioning
confidence: 99%
“…All included studies were case series, among which 15 involved propranolol therapy and 16 used corticosteroids. Twenty‐six studies examined response rates, 12 reported rebound growth rates, 13 analysed spherical power, 14 studies surveyed cylinder power, 16 looked at amblyopia rates after treatment and 21 reported adverse events . Because all of the included studies were observational studies, the MINORS score was applied to define the quality of evidence.…”
Section: Resultsmentioning
confidence: 99%
“…In most studies, propranolol was administered orally at an initial dosage of 0.1–1 mg/kg/day and increased incrementally to 2–3 mg/kg/day . Some studies administered oral propranolol 2 mg/kg/day directly; only one study used 1 mg/mL intralesional propranolol with 0.2 mL/cm and a maximum volume of 1 mL for a 5‐cm lesion …”
Section: Resultsmentioning
confidence: 99%
“…L'efficacité du propranolol administré par voie intralésionelle [45] a été évaluée chez 12 patients (âge moyen 5,9 mois) atteints d'hémangiome périoculaire, versus corticoïdes par voie intralésionelle (groupe contrôle, n = 10). Quatre-vingt-trois pour cent des patients traités par propranolol ont eu une régression de leur hémangiome.…”
Section: Autres Voies D'administrationunclassified